Natural disasters - Alexander, David (Chapman & Hall, 1993)
Here is a comprehensive overview of the geophysical, technological, and social aspects of natural disasters. This book systematically reviews the agents of natural catastrophes - earthquakes, volcanoes, floods, drought, hurricanes, erosion, fires, etc. - in terms of their geophysical processes and effects. The human impact and response is examined from various perspectives, including damage and the urban environment, the logistics of planning and emergency action, medical emergencies and the epidemiology of disasters, the Third World, and socio-economic consequences. The author's unique interdisciplinary perspective helps the reader to achieve a clear perspective on natural disasters and possible strategies against them.